Opium Smoking - The Lascar's Room in "Edwin Drood" - Doré, Gustave (Tufts Archival Research Center, 2006)
This illustration is from Gustave Doré's and Blanchard Jerrold's "Doré's London: London, a Pilgrimage". 'Edwin Drood' refers to an unfinished work by Charles Dickens called "The Mystery of Edwin Drood."